2013
DOI: 10.4161/psb.25027
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of the Golgi apparatus in tobacco BY-2 cells during cell proliferation after release from the stationary phase of growth

Abstract: We have recently developed a new method aimed at mass photo-conversion of photo-convertible fluorescence protein (PFP) fluorescence in transformed tobacco BY-2 cells. Using this method we reported recently that the Golgi apparatus is generated by the de novo formation from ER and the division of pre-existing Golgi stacks with similar extents In this work we report that the proliferation of the Golgi apparatus in tobacco cells that enter the growing cycle from the non-dividing cycle is quite similar to that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Our observations here and our recent analysis of Golgi proliferation using a monomeric KikGR-tagged reporter protein (Abiodun and Matsuoka, 2013a , b ) indicate that bulk conversion of the reporter fluorescence color and subsequent analysis is a method that can be applied to analyze the synthesis and/or turnover of distinct intracellular structures. However, this method has a limitation when used for the quantitative comparison of preexisting and newly synthesized proteins.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our observations here and our recent analysis of Golgi proliferation using a monomeric KikGR-tagged reporter protein (Abiodun and Matsuoka, 2013a , b ) indicate that bulk conversion of the reporter fluorescence color and subsequent analysis is a method that can be applied to analyze the synthesis and/or turnover of distinct intracellular structures. However, this method has a limitation when used for the quantitative comparison of preexisting and newly synthesized proteins.…”
Section: Discussionsupporting
confidence: 52%
“…We have reported that fluorescence of a Golgi-targeted fusion protein comprising of a prolyl-hydroxylase NtP4H1.1 and monomeric KikGR could be converted under illumination by purple light, and this conversion allowed us to monitor the proliferation of the Golgi apparatus in tobacco BY-2 cells (Abiodun and Matsuoka, 2013a , b ). We used the same conversion apparatus (Abiodun and Matsuoka, 2013a ) to convert the fluorescence of the color of the aggregate from green to red.…”
Section: Resultsmentioning
confidence: 99%